The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1051/kmae:2006012
|View full text |Cite
|
Sign up to set email alerts
|

White-Clawed Crayfish in Muddy Habitats: Monitoring the Population in the River Ivel, Bedfordshire, Uk

Abstract: White-clawed crayfish Austropotamobius pallipes are usually associated with stony substrates, tree roots, or refuges in submerged banks. The River Ivel has the last known population of white-clawed crayfish in Bedfordshire. Prior to 2005, much of the bed comprised uniform silt, plus leaf-litter. Stands of reedmace Typha latifolia and other emergent vegetation were localised in less shaded areas. Initial survey results suggested a population at low abundance. A low-cost monitoring strategy was started in 2001 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…These data suggest that ARTs with larger diameters catch more crayfish and have a higher variance in the sizes of crayfish removed. These findings agree with research on white-clawed crayfish (Austropotamobius pallipes Lereboullet, 1858) in the United Kingdom (Peay et al 2006), which demonstrated the positive relationship between opening size in breezeblocks (concrete blocks with pre-constructed holes that provide the same overall function as ARTs in this study) and crayfish size. Specifically, they found that ARTs with 30-mm openings caught more crayfish and crayfish of a wider range of size classes when compared with ARTs with 10-and 15-mm openings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These data suggest that ARTs with larger diameters catch more crayfish and have a higher variance in the sizes of crayfish removed. These findings agree with research on white-clawed crayfish (Austropotamobius pallipes Lereboullet, 1858) in the United Kingdom (Peay et al 2006), which demonstrated the positive relationship between opening size in breezeblocks (concrete blocks with pre-constructed holes that provide the same overall function as ARTs in this study) and crayfish size. Specifically, they found that ARTs with 30-mm openings caught more crayfish and crayfish of a wider range of size classes when compared with ARTs with 10-and 15-mm openings.…”
Section: Discussionsupporting
confidence: 92%
“…With regards to bycatch of non-target organisms, ARTs can generally be deployed in areas with sensitive species, such as salmonid young of year or juvenile amphibians, because they do not have a trapping mechanism that prevents non-target species from escaping (De Palma-Dow et al 2020). On the other hand, in locations where native and non-native crayfish are sympatric, ARTs may be useful for monitoring native populations (e.g., Peay et al 2006) while removing invasive populations (e.g., Green et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannibalism is common in crayfish, with larger adults and juveniles preying on smaller individuals (Abrahamsson, 1966; Mason, 1977), providing opportunities for ingestion of infected tissue. Crayfish use refuges in close proximity to each other as well as coming into contact when foraging and mating (Peay, 2002), providing opportunities for spore transmission via the water. This study also provides the first evidence for direct transmission of T. contejeani from infected white-clawed crayfish to the invasive signal crayfish, both by consumption of infected tissue and through exposure to contaminated water.…”
Section: Discussionmentioning
confidence: 99%